Why Do People Support Online Crowdfunding Charities? A Case Study From China - Jiao, Huifang; Qian, Lamei; Liu, Tianzhuo; Ma, Lijun (Frontiers in Psychology, 2021)
Whereas the effect of people’s motivations to give to traditional, off-line charities has been extensively investigated, their motivations to support online charitable crowdfunding projects are largely unexplored. The present study examines the influences of extrinsic motivations (such as reputation, the wish to signal a certain image; and reciprocity, the expectation on future return for their present contribution), intrinsic motivations (such as a sense of belonging, the feeling of belonging to an integral part of a positive community; joy of giving, the anticipated positive emotions experienced by helping others; altruism, intrinsic desire to help others without expectation of a return; and financial constraints, individuals’ personally felt financial stresses induced by donations), and social interactions (such as social influence, people’s perception of how their close acquaintances believe they should support the project; and social ties, the strength of the relationship between the individual and the project initiator) on intentions to support charitable crowdfunding behaviors, namely, the willingness to share (WTS) project information and the intention to donate (ITD) money. Hierarchical multiple regression analyses on self-reported survey data from 617 respondents in China reveal support for the hypotheses. The results show that intrinsic motivations and social ties are predictors for both supporting behaviors. Reputation and social influence motivate people to share projects, but have no significant effects on their ITD. Reciprocity is positively, and financial constraints are negatively, related to ITD but have no significant effects on WTS. These findings offer insights into the motivations driving individuals’ participation in charitable crowdfunding. The implications for both platforms and fundraisers are discussed.